An Appreciative Inquiry of facilitative factors within educational provision perceived to support engagement of students attending a secondary school-based alternative provision unit - Looney, Elaine (2018)
Rates of school exclusion continue to show annual increase in England (DfE, 2016; DfE, 2017a). Increasingly, there is an impetus to adopt a focus on ‘what works’ to promote educational success for students who experience, or who are ‘at risk’ of school exclusion (e.g. Hart, 2013). The importance of organisational intervention in the prevention of school exclusion is well-cited (e.g. Hallam & Castle, 2001) and gaining the views of students is seen as an essential component of this process (e.g. Cole, 2015).